PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KEUANGAN MELALUI INOVASI DAN KEPUASAN PELANGGAN PADA PERUSAHAAN RETAIL DI SURABAYA - Tjiang, Livia Chandra (Business Accounting Review, 2016)
This study aimed to examine the direct and significant affect of leadership style to innovation, innovation to customerâs satisfaction, customerâs satisfaction to financial performance, leadership style to financial performance, and innovation to financial performance on retail firms in Surabaya. This study used quantitative approach and the data were obtained through the distribution of questionnaires and financial reports of retail firms in Surabaya. The samples used in this study were 18 retail firms in Surabaya listed on Bursa Efek Indonesia 2012-2014, with each of 20 employees and 20 customers of each firm. The data obtained was processed by using SmartPLS software. This study showed that there were a positive and significant relationship of leadership style to innovation, innovation to customerâs satisfaction, customerâs satisfaction to financial performance and leadership style to financial performance. However this study showed that there was a negative and significant relationship of innovation to financial performance on retail firms in Surabaya.